Malles pédagogiques itinérantes « les grands singes et leur habitat »: parcours et premières évaluations de l’impact du projet en Ouganda et au Gabon - Sabrina Krief; Helena Nambogwe; Samy Mankoto; Jean-Michel Krief (Revue de Primatologie)
The Association « Projet pour la Conservation des Grands Singes » in partnership with MNHN, UNESCO and France Cooperation designed Great Apes kits. The showcases contain a set of entertaining and educative tools and activities explaining forests, ecosystems and great apes presented by national educators. The two first kits have moved in Uganda and Gabon in areas located where great apes occur. 15,000 kids from remote areas have already received the programme. In Uganda, 52 primary and secondary schools on a 1,500km tour organised by the Wildlife Clubs of Uganda enhanced greatly the motivation to preserve forests and great apes. In Gabon, the RAPAC together with nine partners involved in environmental education took the kit to 66 schools along another 1,500 km tour. Among those schools some were located in areas controlled by logging companies. In some areas, data on ape meat consumption were obtained. The objectives are to extend the program to others African countries from the home range of Great Apes and to combine it with socio-economic and impact studies.